Performance of soccer passing skills under moderate and high intensity localized muscle fatigue - Lyons, M.; Al-Nakeeb, Y.; Nevill, A. (The Journal of Strength and Conditioning Research, 2006)
Despite the acknowledged importance of fatigue on performance, ecologically sound studies investigating fatigue and its effects on sport-specific skills are surprisingly limited. The aim of this study was to investigate the effects of moderate and high-intensity localized muscle fatigue on passing performance in soccer. Twenty physically active male college students (age, 22.9 ± 5.3 years) participated in this study. Subjects performed the modified Loughborough Soccer Passing Test under the following three conditions: rest, moderate fatigue, and high-intensity fatigue. Fatigue intensity was established using a percentage of the maximal number of alternate split squats performed by the subject in 1 minute. Results revealed a significant difference between performance at rest and performance following high-intensity, localized muscle fatigue. The results suggest the need for trainers and coaches to incorporate high-intensity exercise drills into training plans to help players better cope with the demands of the game on the pitch.